Bargain basement online retail shop application: give and get social entrepreneurship project - Thian, Qi Wee (2022)
Bargain Basement, a charity retail outfit that collects preloved items from the public and resell them at very low prices in brick-and-mortar stores and on its website. However, the daily operation of Bargain Basement physical outlets has affected by the Covid-19 pandemic. Additionally, the current Bargain Basement website has limited functions as an online platform for second-hand sales, which has limited the exposure and awareness of Bargain Basement project to public. To support Bargain Basement project, a cross-platforms online retail shop application was proposed with the development of a mobile-based application for the customers to place orders and a web-based management system for the staffs to manage the online shop. The mobile application provides offer making feature that allows customers bargain with sellers to buy their products at lower prices, while the web-based management system provides features such as product batch uploading and automatic reporting that can help Bargain Basement better manage the online shop. Evolutionary prototyping methodology was chosen as the software development methodology in this project. The requirements were gathered by conducting an interview with the staff of Bargain Basement and also by distributing a questionnaire in the planning and requirement gathering phases. After that, the prototype implementation phase will go through three iterations, and the system prototype was developed at the first iteration and refined at the end of each iteration. After completed the development process, the usability of the system was tested by 12 users, and 90 scores were obtained as the result. In conclusion, a crossplatforms online retail shop application was developed at the end of this project and all the objectives were achieved.